Implementasi Metode Terpadu Ilman Wa Ruuhan Terhadap Sistem Belajar Mengajar Al Qur’an di SDIT Permata Kraksaan Probolinggo - Choerul Anwar Badruttamam (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2022)
Considering the importance of Qur’an purpose in guiding and directing human life, so learning to read, understand and live Qur’an and then practice it in daily life is an obligation for every muslim. To grow love in learning Qur'an requires innovation in learning Qur'an. As is the case in this study which aims to determine the implementation of a method in learning Qur'an, the method is the Integrated Ilman Wa Ruuhan method. Researcher used a type of qualitative research with used a qualitative descriptive approach. Data collection was carried out using in-depth interview techniques, participant observation and documentation, with data sources obtained from school principals and Qur'an teachers at SDIT Permata Kraksaan Probolinggo. In this study, SDIT Permata Kraksaan Probolinggo changed the Qur'an learning method with a new method, namely the Integrated Ilman Wa Ruuhan method, which in this method not only applied ‘Ilman (scientific) Qur'an learning but also Ruuhan (spirituality) applied. The research results obtained that the implementation of the Integrated Ilman Wa Ruuhan method in the process of teaching and learning the Qur'an at SDIT Permata Kraksaan Probolinggo has been effective, with the Qur'an learning process not only ‘Ilman (scientific) which is applied in learning Qur'an but also with Ruuhan (spirituality). So by using the Integrated Ilman Wa Ruuhan method, a feeling of love and desire to become an Expert of the Qur'an is created. Because as Qur'an teachers we don't just come to teach, take attendance and give grades, but how do teachers have a high Ruhaniyah Qur'aniyah so that it can be applied to students.